Az ősleány, az ősistennő és Ariadné elvágott fonala: Antik elemek Hajnal Anna költészetében - Polgár, Anikó (Studia Litteraria, 2022)
The study examines the appearance of mythological point of view and ancient elements in the poems of Anna Hajnal (1907–1977). The first subchapter explores the intertextual background of her early poems written in the 1930s. Anna Hajnal often likens herself to Sappho or addresses the ancient Greek poetess. The second subchapter is concerned with the appearance of ancient quantitative verses. For example, the poem Egy gyermekhez (To a Child) is an imitation of the Sapphic stanza in terms of verse form. The poetess does not consciously follow the Sapphic stanza, it only evokes her memory. The third part analyzes the mythical poems of Anna Hajnal. The poem Tavaszi himnusz (The Hymn of Spring) focuses on the goddess of the moon, who is also the goddess of fertility. The author compares The Hymn of Spring with Anna Lesznai’s poem Tavasz Isten (The God of Spring). The God of Spring rules the forces of nature as the patriarchal father-god, the goddess of spring, on the other hand, brings about change more softly.